Uncertainty analysis of quasi-zero stiffness metastructure for vibration isolation performance - Wang, Dongxian; Zhao, Jianlei; Ma, Qian; Zhou, Gang; Zhang, Duzhou; Zhu, Rui (Frontiers in Physics, 2022)
Quasi-zero-stiffness(QZS) metamaterials and metastructures have great advantages of being highly integratable and lightweight for vibration isolation in aerospace and aviation applications. However, the geometric uncertainty introduced from additive manufacturing (AM) significantly affects the metamaterial/metastructure’s vibration isolation performance and therefore, needs to be evaluated accurately and efficiently in the design process. In this paper, a high-order sparse Chebyshev polynomial expansion (HOSPSCPE) method is first utilized to quantify the influence of AM induced geometric uncertainty in QZS microstructure. Excellent accuracy and much higher efficiency (about 470 times faster) of the proposed method is observed when compared to the widerly used Monte-Carlo method (MCM). Uncertainty analysis are then conducted for vibration isolation performance of the QZS metastructures and the band gap properties of the QZS locally resonant metamaterials, respectively. The numerical results demonstrate that the geometric uncertainty analysis can provide useful guidance and recommendations for the manufacturing influenced design of QZS metastructures and metamaterials.